2016
DOI: 10.2147/iprp.s95733
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the nature of dispensing errors in hospital pharmacies

Abstract: BackgroundDispensing errors are common in hospital pharmacies. Investigating dispensing errors is important for identifying the factors involved and developing strategies to reduce their occurrence.ObjectivesTo review published studies exploring the incidence and types of dispensing errors in hospital pharmacies and factors contributing to these errors.MethodsElectronic databases including PubMed, Scopus, Ovid, and Web of Science were searched for articles published between January 2000 and January 2015. Inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 29 publications
4
60
0
5
Order By: Relevance
“…Approximately 40% of patients who have been discharged from hospital may subsequently experience medicines-related problems, including medicines-related errors. [5][6][7][8][9][10][11][12][13] Findings indicate that patients often lack knowledge about their medications following hospital discharge [14][15][16][17][18] and that many patients report not receiving important medicines-related information. [19][20][21] World Health Organisation policy states that offering information on medicines via Medicines Information Centres, and providing public education about medicines, are two of 12 essential interventions to promote the rational use of medicines.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 40% of patients who have been discharged from hospital may subsequently experience medicines-related problems, including medicines-related errors. [5][6][7][8][9][10][11][12][13] Findings indicate that patients often lack knowledge about their medications following hospital discharge [14][15][16][17][18] and that many patients report not receiving important medicines-related information. [19][20][21] World Health Organisation policy states that offering information on medicines via Medicines Information Centres, and providing public education about medicines, are two of 12 essential interventions to promote the rational use of medicines.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was di cult to assess if all these studies had used the same explicit de nitions as we did to justify comparison. A review on dispensing errors also revealed that dispensing error rates varied between countries (0.015-33.5%) depending on the dispensing system, research method, and classi cation of dispensing error types (29). Our study looked at the full range of errors that could take place in the dispensing process.…”
Section: Discussionmentioning
confidence: 97%
“…Jenis kasus dispensing error yang terjadi pada layanan farmasi adalah salah obat, salah kekuatan obat, dan salah kuantitas. Hal ini selaras dengan beberapa penelitian lain antara lain Aldhwaihi et al (2016), dan James et al (2007). Salah obat adalah jenis error paling umum dari dispensing error pada pelayanan farmasi, sementara error lain adalah kekeliruan kekuatan obat (wrong medicine), dosis (wrong drug strength), dan jumlah obat (wrong quantity) (Aldhwaihi et al, 2016dan James dkk, 2007 selaras dengan temuan penelitian tersebut (Pitoya Z.…”
Section: Kesalahan Menyiapkan Dan Meracik Obat (Dispensing Error)unclassified
“…Hal ini selaras dengan hasil penelitian Aldhwaihi et al (2016) yang menyimpulkan bahwa faktorfaktor yang berkaitan dengan dispensing errors adalah beban pekerjaan tinggi, jumlah staf yang kurang, obat LASA, kemasan yang mirip, sistem penyimpanan obat LASA dan gangguan lingkungan antara lain distraksi, interupsi.…”
Section: Kesalahan Menyiapkan Dan Meracik Obat (Dispensing Error)unclassified